Assessment level and time scales of biodiversity indicators in the scope of the Marine Strategy Framework Directive – A case study for the NE Atlantic. (October 2019) - Machado, Inês; Costa, José Lino; Leal, Miguel Costa; Pasquaud, Stéphanie; Cabral, Henrique
Highlights: Marine Strategy implementation of biodiversity criteria was analysed for two NE Atlantic regions. Bay of Biscay presented higher implementation level in comparison to the Celtic Seas. Bay of Biscay MSs used sparse surveys data, while Celtic Seas MSs reported medium to short term datasets. Marine Turtles and Food webs Groups have wider temporal scope. Descriptors 1 and 3 can be comparable if further temporal synchronization is achieved. Abstract: European Union Member States have made an unprecedent effort to implement the Marine Strategy Framework Directive (MSFD). However, the coherent assessment of Europe's marine waters and Good Environmental Status by 2020 has not yet been achieved. This work analysed the implementation level and time scales used to report biodiversity criteria in the 1 st MSFD cycle for two Biogeographic Regions: the Celtic Seas and the Bay of Biscay and Iberian Platform. Results were compared across Biogeographic Regions, Marine Sub-units, Criteria, and Biological Groups to assess congruency and integration possibilities. Reporting level was significantly different among Marine Sub-units within the same Biogeographic Region and country. France and Spain showed the highest implementation level and focused on criteria included in Biodiversity (1) and Food-Webs (4) Descriptors, while Ireland mostly reported Commercial Fish and Shellfish (3). Fish, Rocky and Biogenic Reefs and Sedimentary Habitat were the most reported Groups. Heterogeneous data was recorded for temporal scales used to report Groups and Criteria among Marine Sub-units within the same region, showing that each MS is working individually. Average temporal range used for reporting was wider in French Bay of Biscay, particularly for Marine turtles' Group, Food-web Criteria (Descriptor 4), and Ecosystem structure criteria ( 1.7 ). Ireland presented consistently shorter temporal data sets focusing on Commercial Fish and Shellfish descriptor (3) and Fish Group. To enable the direct comparisons and integration of MSFD results, the use of historical and opportunistic data should be discouraged, the reporting timeframe of existing monitoring datasets (beginning/end) should be synchronized at regional level, and targeted habitats/species should be decided and prioritized regionally. This work pinpoints MSFD gaps and provides inputs for an improved 2 nd implementation cycle, particularly in what concerns temporal scales used for reporting.